A Case of Nonunion Avulsion Fracture of the Anterior Tibial Eminence - Satoru Atsumi; Yuji Arai; Shuji Nakagawa; Hiroaki Inoue; Kazuya Ikoma; Hiroyoshi Fujiwara; Toshikazu Kubo (Case Reports in Orthopedics)
Avulsion fracture of the anterior tibial eminence is an uncommon injury. If bone union does not occur, knee extension will be limited by impingement of the avulsed fragment and knee instability will be induced by dysfunction of the anterior cruciate ligament (ACL). This report describes a 55-year-old woman who experienced an avulsion fracture of the right anterior tibial eminence during recreational skiing. Sixteen months later, she presented at our hospital with limitation of right knee extension. Plain radiography showed nonunion of the avulsion fracture region, and arthroscopy showed that the avulsed fragment impinged the femoral intercondylar notch during knee extension. The anterior region of the bony fragment was debrided arthroscopically until the knee could be extended completely. There was no subsequent instability, and the patient was able to climb a mountain 6 months after surgery. These findings indicate that arthroscopic debridement of an avulsed fragment for nonunion of an avulsion fracture of the anterior tibial eminence is a minimally invasive and effective treatment for middle-aged and elderly patients with a low level of sports activity.